Effect of phosphorus and potassium fertilization on summer greengram (Vigna radiata) varieties - BAITE, N ANTHONY; NONGMAITHEM, D; D, SAYA; SENTISUBA; AIER, IMNATEMJEN (The Indian Journal of Agricultural Sciences, 2023)
This experiment suggests that the utilization of the greengram variety IPM 02-3 is advantageous due to its superiority in terms of performance and adaptability over other varieties investigated. Additionally, application of 50 kg/ha P2O5 and K2O demonstrates comparable performance and profitability to application of 60 kg/ha P2O5 and K2O, making it an economically favourable option. Soil fertility analysis revealed P and K’s role in enhancing nutrient dynamics. The relation between soil nutrient levels and greengram yield underscores the multifaceted relationship. In summary, genetic factors, coupled with optimal nutrient management, synergistically affect the growth and yield of greengram.